Under the Radar—The Return of Member States in EU Investment Policy. (12th October 2022) - Bungenberg, Marc; Böhme, Bianca
ABSTRACT: While the investment agreements concluded by the EU have not entered into force, its Member States' bilateral treaties have become a new vehicle to implement EU investment policy in a decentralized fashion. To that end, the EU is planning to use model clauses and interpretative guidelines to be followed by its Member States in their investment agreements. This article argues that this approach has significant benefits but also considerable costs of fragmentation. On the one hand, a decentralized EU investment policy enhances the exportation of EU values, contributes to level the playing field among the Member States, and leads to further integration in that area. On the other hand, the decentralized approach has important downsides: it requires multiple costly treaty (re-)negotiations and the abandonment of the EU's competence-based allocation of international responsibilities. A plurilateral (re-)negotiation is the better approach, with the same benefits but no costs of fragmentation.